Pelanggaran Etika Pariwara Indonesia dalam Iklan Luar Griya di Jalan Godean Sleman Daerah Istimewa Yogyakarta - Sukhfi, Muhammad Adnan; Setiaputra, Rizky; Pramudita, Antik; Ananda, Dhimas Aryo Vipha (Jurnal Audiens, 2025)
This study evaluates violations of the Indonesian Advertising Ethics in outdoor advertisements along Godean Street, Yogyakarta, covering aesthetic, construction, environmental, and spatial planning aspects. Using a qualitative descriptive approach, the research documentation methods. Findings reveal significant violations, such as non-aesthetic advertisement designs, unsafe constructions, environmental damages, and placement breaching spatial regulations. Lack of supervision and awareness of Etika Pariwara Indonesia are the main contributing factors. This study highlights the importance of strengthening regulations and awareness campaigns to create responsible advertising and support environmental sustainability.